A Review on kayakatpamooligaikal (Rejuvenating herbs) which are using in the siddha medicine - Piramila, U.; Krishanthy, T.; Vinotha, S. (University of Colombo, 2017)
Kayakatpam formulated by the great Siddars who are introduce the Siddha system of Medicine in the world several thousand years ago. Kayakatpam literally means, a power of health securing the body as to keep the Kayam as form as stone. Kayakatpam is divided in to Pothu and Sirappukayakatpam. The Pothu and Sirappukayakatpam are beneficial for strengthening the body and against specific diseases respectively. Siddha text books were mentioned 108 names of Kayakatpamooligaikal (K.Mooligaikal). The aim of this study was to review the important characters of Kayakatpamooligaikal which are using in Siddha Medicine. Data were collected from the related text books and research articles. In this present study, the parts use, Siddha properties such as taste, potency and efficacy, phytochemicals and pharmacological actions for the 41 K. Mooligaikal which were mentioned in the Siddha texts were reviewed. The results showed that, among the 41 K. Mooligaikal 78% (32) were categorized as Sirappuk. Mooligaikal which are belong to different families and 43.90% (18); 36.58% (15) and 34.14% (14) were used as leaves, unripe fruits and roots respectively. This K. Mooligaikal contains siddha properties {sweet and bitter taste 39.02% (16); cold potency 53.65% (22) and sweet efficacy 51.21% (21)}, phytochemicals {flavonoids 60.97% (25), alkaloids 56.09% (23) and tannins 48.78% (20)} and pharmacological actions {anti inflammatory 48.78% (20), antioxidant and diuretic 43.90% (18) and alternative 34.14% (14)}. Although, this review can be provide useful informative supports for application of K. Mooligaikal in health management further extensive scientific studies should be carried out in future.
Keywords: Kayakatpam; Mooligaikal; Rejuvenation; Siddha medicine